The Distribution of Schools Not Served by BRT Trans Semarang in Semarang City - Sari, Nanda Iryani Intan; Soehodho, Sutanto; Sumabrata, R. Jachrizal (UI Scholars Hub, 2024)
For developing countries, the implementation of sustainable transportation systems is crucial to involve substantial investments. Mobility in Indonesia can have an impact on both origin and destination areas. This research aims to determine the distribution of schools that are not served in the city of Semarang. Consequently, an identification can be made to formulate a recommendation for the development of operational routes for the BRT Trans Semarang to enhance connectivity between other transportation modes on routes with high demand. A quantitative descriptive analysis was performed to assess BRT Trans Semarang through utilizing government documents, news, and official websites, followed by interviews, FGD, and direct surveys with BRT users and providers. It is known that there are a number of schools that are not served in 16 districts of the city of Semarang, namely Semarang West (51), Semarang South (25), Semarang Central (41), Semarang East (36), Semarang North (40), Banyumanik (49), Tembalang (36), Gunung Pati (16), Pedurungan (50), Gajah Mungkur (31), Mijen (26), Candisari (21), Tugu (14), Gayamsari (25), Ngaliyan (27), and Genuk (29). Feeder Route 3 is popular but has limited capacity. 79.20% of respondents support extending BRT routes to their schools.